Monitoring of Pre-Load on Rock Bolt Using Piezoceramic-Transducer Enabled Time Reversal Method - Linsheng Huo; Bo Wang; Dongdong Chen; Gangbing Song (Sensors, 2017)
Rock bolts ensure structural stability for tunnels and many other underground structures. The pre-load on a rock bolt plays an important role in the structural reinforcement and it is vital to monitor the pre-load status of rock bolts. In this paper, a rock bolt pre-load monitoring method based on the piezoceramic enabled time reversal method is proposed. A lead zirconate titanate (PZT) patch transducer, which works as an actuator to generate stress waves, is bonded onto the anchor plate of the rock bolt. A smart washer, which is fabricated by sandwiching a PZT patch between two metal rings, is installed between the hex nut and the anchor plate along the rock bolt. The smart washer functions as a sensor to detect the stress wave. With the increase of the pre-load values on the rock bolt, the effective contact surface area between the smart washer and the anchor plate, benefiting the stress wave propagation crossing the contact surface. With the help of time reversal technique, experimental results reveal that the magnitude of focused signal clearly increases with the increase of the pre-load on a rock bolt before the saturation which happens beyond a relatively high value of the pre-load. The proposed method provides an innovative and real time means to monitor the pre-load level of a rock bolt. By employing this method, the pre-load degradation process on a rock bolt can be clearly monitored. Please note that, currently, the proposed method applies to only new rock bolts, on which it is possible to install the PZT smart washer.